2011
DOI: 10.1055/s-0030-1270071
|View full text |Cite
|
Sign up to set email alerts
|

Antiphospholipid Syndrome: Endocrinologic Manifestations and Organ Involvement

Abstract: Antiphospholipid syndrome (APS) is a systemic autoimmune disease characterized by thrombotic tendency that affects most organ systems in the human body. In this report, we present a review of the endocrinologic manifestations associated with APS by evaluating the medical literature from 1968 to 2009 using MEDLINE and these keywords: APS, antiphospholipid syndrome, antiphospholipid antibodies, anticardiolipin antibodies, lupus anticoagulant, anti β-2 glycoprotein I, pituitary, adrenal, thyroid, parathyroid, ova… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 47 publications
(53 reference statements)
0
34
1
1
Order By: Relevance
“…Analysis of manifestations of APA depending on the presence and manifestation of psychosomatic disorders indicated that the frequency of significant APA titers in patients with infertility and psychosomatic disorders was two times higher and equaled 44.3% against 18.9% (P < 0.05). We found no similar data in the available literature, but such result can be explained by close relationship with various somatic pathology, particularly endocrine and cardiovascular pathology (Mehdi et al, 2011;da Silva et al, 2014).…”
Section: Discussioncontrasting
confidence: 73%
“…Analysis of manifestations of APA depending on the presence and manifestation of psychosomatic disorders indicated that the frequency of significant APA titers in patients with infertility and psychosomatic disorders was two times higher and equaled 44.3% against 18.9% (P < 0.05). We found no similar data in the available literature, but such result can be explained by close relationship with various somatic pathology, particularly endocrine and cardiovascular pathology (Mehdi et al, 2011;da Silva et al, 2014).…”
Section: Discussioncontrasting
confidence: 73%
“…One of the reviews highlighted studies which described increases in the frequency of aPL antibodies in the serum of diabetic patients implying macroangiopathic complications, besides the finding of aCL IgG antibodies in the serum of first-degree relatives of diabetic patients. On the other hand, another literature review highlighted the need for further studies to clarify the relationship between aPL and diabetes mellitus, one time found no consistent data on the prevalence and significance of aPL in diabetes mellitus [33, 34]. …”
Section: Traditional Risk Factorsmentioning
confidence: 99%
“…Water metabolism disturbances in patients with Sheehan's syndrome depend on several factors such as the degree of pituitary damage, the time of onset since the pituitary injury, association of co-morbidities and/or concomitant medication. Emerging evidence shows that Sheehan's syndrome with or without diabetes insipidus is increasingly reported in association with antiphospholipid syndrome (Mehdi et al, 2011). In addition, in advanced pregnancy, contribution of enhanced vasopressinase activity to disturbed water balance should be considered and is suggested by incomplete response of polyuria and polydipsia to vasopressin but adequate control by desmopressin.…”
Section: Sheehan's Syndromementioning
confidence: 99%